The Effect of Hitting Ball Practice on the Ability of Jump Service Athletes of Men Excludes of Xaverius 3 Palembang High School - Ana, Marcelina Garcia; Manullang, Jujur Gunawan; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study was to determine the effect of hanging ball hitting practice on the ability to jump service in male athletes at Xaverius 3 Palembang extracurricular high school. The formulation of the problem in this study is whether there is an effect of hanging ball practice on the jump service ability of male athletes at Xaverius 3 Palembang High School. This research was conducted on male extracurricular athletes from Xavier 3 Palembang High School. The research method used is Quasi Experimental Design, namely by using a pretest-posttest design group plan, this research is objective, namely because the athlete sample is 20 people so that it is a sample of the entire population (total sampling). The results of the calculated significance data of 0.000 proved to be less than 0.05, and the results of the t test showed that the t value was 8.335 greater than t table; then the hypothesis is accepted that there is a significant effect of hanging ball hitting practice which can increase the ability to jump service in male athletes at Xaverius 3 Palembang extracurricular high school.